Functional food products with immunocorrective action - Starovoitova, Svitlana; Karpov, Alexander (My University, 2016)
Modulation of immunological reactivity - one of the important mechanisms of probiotic microorganisms that can be the basis for the differentiated application of functional food products and probiotic for the prevention and treatment of diseases.
Keywords: functional food products; immunocorrective action; lactic acid bacteria; функціональні харчові продукти; імунокорегувальна дія; молочнокислі бактерії; кафедра біотехнології і мікробіології; функциональные продукты питания; иммунокорректирующее действие; молочнокислые бактерии